Numerical Solution of Fractional Pantograph Differential Equation via Fractional Taylor Series Collocation Method - Bilal, Muhammad; Norhayati, Rosli; Norazaliza, Mohd Jamil; Ahmad, Ifthikar (Universiti Putra Malaysia, 2020)
In this paper, a collocation method which based on polynomial approximation of Taylor's series is proposed to approximate the solution of fractional pantograph differential equations (FPDE). The collocation method with truncated Taylor's polynomial is shown to be an applicable technique in solving FDDE. Some examples of the non-linear fractional pantograph differential equations are solved and compared with the exact solution to confirm the accuracy and applicability of the collocation method with Taylor's polynomial.